Seagrass community data derived from field surveys at Hera Bay, Timor-Leste, conducted 30 November 2022 and 08 March 2023 - Jemima Gomes; Cecilia Lay; Patricio Ximenes; Advento F Dos Reis Pereira; Joãozinho Dedito Martins; Nelson Amaral; Alex Bartlett; Ryan Lewis; Lucas Langlois; Rudi L Yoshida; Len McKenzie (PANGAEA, 2025)
The area of interest of approximately 590 ha was surveyed by boat and by foot at low tide between 30th October 2022 and 8th March 2023, resulting in 275 spot-checks. For the boat-based subtidal surveys, at each mapping point, a GoPro® drop–camera assembly (incl. frame with 0.25 m2 quadrat in field of view), was used to visually assess the seabed and the photoquadrat footage captured for post-field analysis. Within a 3 m radius of an individual point, between 1 and 4 geo-located photoquadrats were collected (742 total). Subtidal assessments were conducted using a real time drop-camera slaved to a surface tablet, to ensure photoquadrats were sufficiently spaced apart and the vision captured was suitable for post-field analysis. For the foot-based intertidal surveys, at each mapping point, a spot-check was conducted by collecting three photoquadrat taken haphazardly within 5-10 m2 area. All individual photoquadrats were assessed for seagrass percentage cover, species composition, sediment classification, macroalgae abundance and epiphyte abundance. These various data fields were then aggregated for each mapping point by taking the mean of the numerical fields and most occurring value for the text field. Additional mapping points were included from Seagrass Spotter.